Sleep restriction caused impaired emotional regulation without detectable brain activation changes—a functional magnetic resonance imaging study. Issue 3 (27th March 2019) - Tamm, Sandra; Nilsonne, Gustav; Schwarz, Johanna; Golkar, Armita; Kecklund, Göran; Petrovic, Predrag; Fischer, Håkan; Åkerstedt, Torbjörn; Lekander, Mats
Abstract : Sleep restriction has been proposed to cause impaired emotional processing and emotional regulation by inhibiting top-down control from prefrontal cortex to amygdala. Intentional emotional regulation after sleep restriction has, however, never been studied using brain imaging. We aimed here to investigate the effect of partial sleep restriction on emotional regulation through cognitive reappraisal. Forty-seven young (age 20–30) and 33 older (age 65–75) participants (38/23 with complete data and successful sleep intervention) performed a cognitive reappraisal task during fMRI after a night of normal sleep and after restricted sleep (3 h). Emotional downregulation was associated with significantly increased activity in the dorsolateral prefrontal cortex ( p FWE < 0.05) and lateral orbital cortex ( p FWE < 0.05) in young, but not in older subjects. Sleep restriction was associated with a decrease in self-reported regulation success to negative stimuli ( p < 0.01) and a trend towards perceiving all stimuli as less negative ( p = 0.07) in young participants. No effects of sleep restriction on brain activity nor connectivity were found in either age group. In conclusion, our data do not support the idea of a prefrontal-amygdala disconnect after sleep restriction, and neural mechanisms underlying behavioural effects on emotional regulation after insufficient sleep require further investigation.